Influence of TESPT on Tensile and Tear Strengths of Vulcanized Silica-filled Natural Rubbe - A.K. NORIZAH; S. AZEMI (ASEAN Journal on Science and Technology for Development, 2017)
The effectof coupling agent on tensile and tear strengthsof vulcanized NR filledwith 50 pphr of precipitated silica (VN3) was investgated. The amount of coupling agent was varied from 0,1,2,3,4,5 to 8 pphr. In the absence of coupling agent bis[3-(triethoxysilyl)propyl] tetrasulphide (TESPT), the tensile strengthof silica-fille vulcanized NR was lower than the tensile strengthof unfilledvulcanized NR. The enhancement in the tensile strengthwas achieved only when TESPT was incorporated into the rubber compound. The dependence of tensile strengthon the amount of TESPT showed a similar trend as the dependence of tensile strengthon the crosslink concentration. This might imply that varying the amount of TESPT was analogous to varying the crosslink concentration of the rubber network. The effct of TESPT on tearing energy was very strking in silica-filed vulcanized NR. Without Si69, the crack propagated in a steady(smooth) manner where the tearing energy increases with increasing testspeed. When TESPT was added into the silica mix, the crack propagated sideways from the intended tear path producing the so called knotty tearing. The tearing energy was about a factor of ten higher than that without coupling agent in particular at low tear rates regions. The results here indicated clearly that in silica-filledvulcanized NR, coupling agent was essential to induce the strengthanisotropy necessary for the occurrence of knotty tearing. The result also showed that TESPT also influencedthe amount of hysteresisin silica-filledvulcanized NR. Both tensile and tear strengths were affected by the hysteresi